Implikasi Model Discovery Learning Berbasis Pendekatan Saintifik Pada Materi Sikap Terpuji - Sri Juwita; Mutia Alhaq; Neng Vera Fachriyah; Irawan (LP. Ma'arif Janggan Magetan, 2022)
This study aims to determine the effect of the discovery learning model based on a scientific approach to the subject matter of commendable attitudes. This research was carried out in learning Islamic religious education in class IV of SD Ashfiya. The research method used is a quasy experiment with a pretest posttest design. The sample in this study was class IV A, totaling 20 people as the experimental class and class IV C, totaling 20 people as the control class. The results showed that the average score between the pretest and posttest in the experimental class through the t-test was higher, namely 39.25 compared to the control class which obtained a value of 30.75. The average post-test score for the experimental class was 85.25 and the control class scored 75.50. The gain test value obtained by the experimental class was 0.72 while the control class was 0.56. The experimental class scores are in the high category, while the control class is in the medium category. The results showed that the learning model of discovery learning had a significant influence on student learning outcomes in commendable attitude material.